First-party and third-party food delivery apps, which is better in Indonesia? - Kartika Aprilia Benhardy; Matthew Ronadi (Journal of Business Studies and Management Review, 2020)
Indonesia is a nation with considerable GDP growth because of high household consumptions. One of the contributors to household consumption is eating out, which drives the growth of online ordered food in Indonesia. Ordering food online can be done through a website and via application of that restaurant (first-party) or through third-party food delivery apps. This research wants to investigate further what factors are considered by the consumer when choosing an online food delivery app and also deciding if consumers prefer to use first-party or third-party food delivery apps. The field of this research is limited to Pizza Delivery Apps, and Analytic Hierarchy Process (AHP) is used to determine which factors are the most considered by consumers when choosing an application. The respondents of this research are just five people who have used pizza delivery apps in the past few months, and a geometric mean calculated to analyze the results. The results show that Trustworthiness and E-Service Quality are the most considered factors by consumers when choosing a food delivery app. Consumers highly consider first party food delivery apps which are PHD and Domino’s Pizza become the choice of consumers because of higher Trustworthiness factors. Third-party food delivery apps, which are Go-Jek and Grab, were rated by consumers to have a lower trust factor compared to first-party apps. This research shows food delivery apps by a restaurant (first-party) has it is own advantage compared to third-party food delivery apps.